Condylar Changes in Children with Posterior Crossbite after Maxillary Expansion: Tridimensional Evaluation - Rosamaria Fastuca; Helga Turiaco; Fausto Assandri; Piero A. Zecca; Luca Levrini; Alberto Caprioglio (MDPI AG, 2021)
(1) Background: To investigate condylar position in subjects with functional posterior crossbite comparing findings before and after rapid maxillary expansion (RME) treatment through 3D analysis; (2) Methods: Thirty-two Caucasian patients (14 males, mean age 8 y 8 m ± 1 y 2 m; 18 females mean age 8 y 2 m ± 1 y 4 m) with functional posterior crossbite (FPXB) diagnosis underwent rapid palatal expansion with a Haas appliance banded on second deciduous upper molars. Patients' underwent CBCT scans before rapid palatal expansion (T0) and after 12 months (T1). The images were processed through 3D slicer software; (3) Results: The condylar position changes between T1 and T0 among the crossbite and non-crossbite sides were not statistically significant, except for the transversal axis. At T1, the condyles moved forward (y axis) and laterally (x axis), they also moved downward (z axis) but not significantly; (4) Conclusions: Condilar position in growing patients with functional posterior crossbite did not change significantly after rapid maxillary expansion.